Role of Large Cabbage White butterfly male-derived compounds in elicitation of direct and indirect egg-killing defenses in the black mustard - Fatouros, Nina E.; Paniagua Voirol, Luis R.; Drizou, Fryni; Doan, Quyen T.; Pineda, Ana; Frago, Enric; van Loon, Joop J. (Frontiers in Plant Science, 2015)
To successfully exert defenses against herbivores and pathogens plants need to recognize reliable cues produced by their attackers. Up to now, few elicitors associated with herbivorous insects have been identified. We have previously shown that accessory reproductive gland secretions associated with eggs of Cabbage White butterflies (Pieris spp.) induce chemical changes in Brussels sprouts plants recruiting egg-killing parasitoids. Only secretions of mated female butterflies contain minute amounts of male-derived anti-aphrodisiac compounds that elicit this indirect plant defense. Here, we used the black mustard (Brassica nigra) to investigate how eggs of the Large Cabbage White butterfly (P. brassicae) induce, either an egg-killing direct (i.e. hypersensitive response (HR)-like necrosis) or indirect defense (i.e. oviposition-induced plant volatiles attracting Trichogramma egg parasitoids). Plants induced by P. brassicae egg-associated secretions expressed both traits and previous mating enhanced elicitation. Treatment with the anti-aphrodisiac compound of P. brassicae, benzyl cyanide, induced stronger HR when compared to controls. Expression of the salicylic (SA) pathway- and HR-marker PATHOGENESIS-RELATED GENE1 (PR1) was induced only in plants showing an HR-like necrosis. Trichogramma wasps were attracted to volatiles induced by secretion of mated P. brassicae females but application of benzyl cyanide did not elicit the parasitoid-attracting volatiles. We conclude that egg-associated secretions of Pieris butterflies contain specific elicitors of the different plant defense traits against eggs in Brassica plants. While in Brussels sprouts plants anti-aphrodisiac compounds in Pieris egg-associated secretions were clearly shown to elicit indirect defense, the wild relative B. nigra, recognizes different herbivore cues that mediate the defensive responses. These results add another level of specificity to the mechanisms by which plants recognize their attackers.